THE CHALLENGE IDENTIFICATION OF GOVERNMENT ACCOUNTANT IN VIRTUAL ERA - Persulessy, Grace; Kusumawati, Dr. Andi; Nirwana, Dr. Nirwana (jfpublisher, 2022)
This research aim to identify the problems and challenges of their accountants working in virtual technology era. The author believes that identifying the challenges government accountants face in this technological era will make it easier for them to work to serve the public. This study depends on the results of scientific studies as evidence of the kingdom of the field and analyzed under a phenomenological approach then we can present a valid and convincing finding in answering the problems of this research. The review processes conducted by researchers are data coding, evaluation, and in-depth interpretation to get valid findings. The data obtained from several literature sources through an electronic search system by installing keywords. From the study results and discussion, it concludes that the challenges faced by public accountants include the importance of them mastering technology and understanding how the public desires services. In other words, the challenge of the public accounting profession in globalization era is the liberalization of accounting services. These obstacles will result in the importance of education and qualifications that necessary for public accounting services. It is hoped that these findings will become an essential part of future policymaking.